Revitalisasi Peran Pusdiklat Pajak Sebagai Tax Mediation Unit (TMU): Mekanisme Alternative Dispute Resolution (Adr) Dalam Sistem Perpajakan Indonesia - Muh. Tunjung Nugroho; Mohammad Djufri; Taufik Kurachman (Jurnal Pajak dan Bisnis, 2026)
Abstract Indonesia’s self-assessment tax system emphasizes voluntary compliance as a fundamental pillar for effective revenue collection. In this context, the quality of interaction between taxpayers and tax authorities plays a crucial role in shaping trust and administrative effectiveness. This study develops the concept of a Tax Mediation Unit (TMU) as an institutional innovation designed to bridge this relationship through a dialogic, participatory, and non-adversarial approach. The research adopts a conceptual framework integrating the Slippery Slope Framework, procedural justice theory, information asymmetry theory, and Alternative Dispute Resolution (ADR), supported by international comparative analysis. The findings highlight that positioning the TMU within the Tax Training Center (Pusdiklat Pajak) as a semi-independent institution provides advantages in terms of neutrality, academic capacity, and an educational approach. TMU contributes to improving dispute resolution processes, reducing information asymmetry, and strengthening trust and procedural justice. Its implementation is expected to enhance voluntary compliance, reduce dispute escalation, and support the transformation toward a more fair, efficient, and trust-based tax system. Keywords: Tax mediation, Tax Mediation Unit, voluntary compliance, procedural justice, information asymmetry, ADR, trust-based tax system